the Traditional Balinese Umbrella Medium in the Exploration of Contemporary Art: Medium Payung Tradisional Bali Dalam Eksplorasi Seni Rupa Kontemporer - I Made Adi Udayana; I Wayan Adnyana; I Wayan Mudana (Gorga : Jurnal Seni Rupa, 2025)
The creation of contemporary art using traditional Balinese umbrellas as a medium is an effort to explore various issues currently affecting the agricultural sector and the need to develop strategies to address them. This creation is clearly an effort to reintroduce existing cultural heritage. The discovery of ideas and concepts in creation began by observing the phenomena occurring in the community, particularly in agricultural areas today, and then through critical reflection, finding the connection between the existence of Payung Uang and Lunas and the creation of contemporary artworks that often stem from current social issues. Based on this, the creative idea was formulated: (1) How does the process of creating and shaping contemporary visual art based on the exploration of the traditional Balinese umbrella medium occur? The artwork is expressed through visual language by uniting objects to achieve the intended concept. The creative method used involves several stages: exploration, design, and formation. The formation process is described through several artistic stages, such as: 1. Initial coloring (imprimatura), 2. Coloring, 3. Finishing. The creation of contemporary art resulted in sixteen works divided into three major works titled: 1) Concrete Area, 2) Narrated Landscape.